PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN PKn SISWA KELAS III SDN TIMBUL SLOKO 01 DEMAK - Fine Reffiane; Wahyu Ariyanto (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2015)
Learning model that is able to realize the situation of teaching and learning process in schools as more activities to enable students to read and solve problems on their own under the supervision and guidance of teachers. Selection of this model can be done through an active and creative collaboration between teachers and students. One model that can be done is an active learning model that is humane, participatory, and attention to the diversity of students in the learning process. Based on the results of the learning process Civics class III, then learning problems Civics is still a serious problem. This is evident from analysis of daily tests with an average value of only 55 who have not reached the minimum completeness criteria that has been set is 65. This indicates that the learning process Civics third grade students are less effective. Caused by several classical problems one of them because the learning model Civics less varied and rarely involve students in the learning process.Student learning outcomes in the first cycle to obtain the average grade 65, increased in the second cycle be 79. The individual study results also increased from the first cycle to the second cycle. Classroom atmosphere becomes more pleasant and conducive, and not boring for students. This is because the use of the learning model Make A Match effective. Increased activity of students of the first cycle of 47% to 75% in the second cycle. Interest and motivation of students towards subjects Civics become higher so that students become more active and creative in the learning process. Teacher performance to be better in the learning process with a model of Make A Match.Make A Match approach can improve student learning outcomes of the subjects Civics, active students in following the teaching Civics and student motivation against Civics, then the school can implement the same strategy for improving student learning outcomes in other subjects. It should be for Civics teachers to strive and implement a variety of models and a variety of learning methods, among others Make A Match making Civics as a lesson favored, exciting, and not boring for students.